ANALISIS MULTI KRITERIA PENDANAAN PEMBANGUNAN JEMBATAN GANTUNG DENGAN ANGGARAN PENDAPATAN DAN BELANJA NEGARA (APBN) - Frias Rusinta; Julistyana Tistogondo (Fakultas Teknik, Universitas Wiraraja, 2022)
As a part of the Nawa Cita program of the President of the Republic of Indonesia, the suspension bridge construction program is building Indonesia from the periphery by strengthening regions and villages within the framework of the unitary state. The construction of suspension bridges is intended to assist local governments and communities in overcoming problems such as improving inter-village development, alleviating centralized regional development, cutting down limited access to inter-village transportation that has not been connected with education, health facilities, or other facilities, as infrastructure for disaster mitigation or evacuation, as well as development Inadequate infrastructure for isolated villages and outermost villages. Setting priorities for the proposals of construction of a suspension bridge for pedestrians need the criteria and judgments that will simplify the determination of the priority of the suspension bridge proposal. The criteria and judgment need to be substantiated scientifically, by applying Analytical Hierarchy Process (AHP) method in determining the priority of the proposals. From this study, we can interpret that the benefit of the bridge to economic activity has the biggest percentage 26.50% of the overall importance of the criteria and on the other hand, administrative requirements have the smallest percentage 6.34% of the overall importance of the criteria. Keywords:AHP,regional infrastructure, suspension bridge, priority.